GE_GERICHTE P/9993/2017 vom 2. August 2018 - GE Cour de justice (2018)
BRIGANDAGE ; VOL(DROIT PÉNAL) ; VIOLENCE CONTRE LES AUTORITÉS ; CONSOMMATION DE STUPÉFIANTS ; EXPULSION(DROIT PÉNAL) ; DÉFENSE D'OFFICE | CP.140.ch1; CP.139; CP.285.al1 et 2.ch1; CP.66a.al1; LStup.19a.ch1; CEDH.8; CPP.135.al1